OC-043 Long term efficacy and safety of ustekinumab for crohn's disease: results from im-uniti long-term extension through 2 years. (17th June 2017) - Sandborn, WJ; Rutgeerts, P; Gasink, C; Jacobstein, D; Gao, L; Johanns, J; Sands, B; Hanauer, S; Targan, S; Ghosh, S; Villiers, WJS de; Colombel, JF; et al.
Abstract : Introduction: Ustekinumab (UST) is a fully human mAB to IL–12/23 p40 approved for treatment of moderate-severe active Crohn's disease (CD). The IM-UNITI long-term extension (LTE) evaluates efficacy and safety of subcutaneous (SC) UST through approximately 5 years of treatment, with wk96 results reported herein. Method: 1281 patients (pts) entered the maintenance study, including 397 UST induction responders in the primary IM-UNITI population. PBO induction responders continued on PBO, PBO induction non-responders received UST 130 mg IV then UST 90 mg SC q12w if in clinical response at wk8, and UST induction non-responders received UST 90 mg SC and if in clinical response at wk8 continued on UST 90 mg q8w. All pts completing wk44 were eligible to enter LTE continuing their treatment regimen, including 567 UST pts. Results: Table 1 presents analyses for randomised pts where pts missing data/discontinued are assumed not to be in response/remission at wk92, with 72.6% of q12w pts and 74.4% of q8w pts achieving remission at wk92. Baased on observed data analyses, among randomised pts who continued to receive UST through wk96, 79.2% of q12w and 87.1% of q8w pts were in remission and 90.9%–94.3% were in response at wk92, respectively. Among all UST treated pts who continued to receive UST through wk96, remission and response rates at wk92 were 70.7%–84.7%. Safety events were not higher among UST treated pts vs PBO through wk96, including overall AE's (82.9 vs 91), SAE's (14.16 vs 18.2), and serious infections (3.73 vs 4.33). Among UST treated pts, there were 2 deaths (sudden death, asphyxia). Two non-NMSC malignancies were reported, a seminoma (UST) and a papillary thyroid cancer (PBO only). Conclusion: SC UST maintained clinical response and remission through two years. No new safety signals were observed. Disclosure of Interest: None Declared